2011
DOI: 10.5194/osd-8-2417-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-dimensional modelling of wave-induced current from the surf zone to the inner shelf

Abstract: We develop and implement a new method to take into account the impact of waves into the 3-D circulation model SYMPHONIE (Marsaleix et al., 2008, 2009a), following the simplified equations of Bennis et al. (2011) which use glm2z-RANS theory (Ardhuin et al., 2008b). These adiabatic equations are completed by additional parameterizations of wave breaking, bottom friction and wave-enhanced vertical mixing, making the forcing valid from the surf zone through to the open ocean. The wave forcing is performed by wave … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 79 publications
3
21
0
Order By: Relevance
“…In particular, the radiation stresses were 1 order of magnitude smaller than the dominant acceleration, pressure gradient and frictional terms, consistent with other studies that ignored wave forcing outside the surf zone (Lentz et al, 1999;Fewings and Lentz, 2010). In a region 150 km north of our study area, in water depths of 28 m off the Tet River, Michaud et al (2012) confirmed numerically that the wave effects on the inner-shelf circulation are relatively small even during a storm event.…”
Section: Momentum Evolution In the Inner Shelfsupporting
confidence: 91%
“…In particular, the radiation stresses were 1 order of magnitude smaller than the dominant acceleration, pressure gradient and frictional terms, consistent with other studies that ignored wave forcing outside the surf zone (Lentz et al, 1999;Fewings and Lentz, 2010). In a region 150 km north of our study area, in water depths of 28 m off the Tet River, Michaud et al (2012) confirmed numerically that the wave effects on the inner-shelf circulation are relatively small even during a storm event.…”
Section: Momentum Evolution In the Inner Shelfsupporting
confidence: 91%
“…The 30 vertical levels were irregularly distributed, with increased resolution near the sea surface. The horizontal grid corresponded to the orthogonal curvilinear system used by Michaud et al [2012] with the pole of the grid at 37.5°N, 140°E, corresponding to the center of the circle shown on Figure 1. The horizontal resolution was variable and increased linearly with the distance from the Fukushima NPP, where the size of the grid mesh was about 600 m. At the open lateral boundaries, the horizontal resolution reached its maximum value of 5.5 km.…”
Section: Methodsmentioning
confidence: 99%
“…Based on Michaud et al . [], the surface boundary condition for the turbulent equation in the coupled model is expressed by Kq(q2/2true)z=ϕoc at z=0, where Kq is the mixing coefficient. In addition, the surface length scale is set as l0=κz0, where κ=0.4 is the von Karman's constant.…”
Section: The Coupled Wave‐circulation Modelmentioning
confidence: 99%